Environmental management practices in the Lebanese pharmaceutical industries: - Ramadan, W. (2015)
This research attempts to provide an understanding of the Lebanese pharmaceutical industries’ environmental management strategies, priorities, and perceptions as well as drivers, barriers, and incentives regarding the implementation of the voluntary ISO 14001 Environmental Management System. Accordingly, a semistructured in-depth interview was conducted with the pharmaceutical industries. The findings revealed a significant lack of knowledge about the standard among the industries. The main perceived drivers for adopting the ISO 14001 are improving the companies’ image and overcoming international trade. The main perceived barriers for acquiring the standard are the lack of government support and the fact that ISO 14001 is not being legally required or enforced by the government. Moreover, results revealed that adopting the ISO 14001 standard is not perceived as a priority for the Lebanese pharmaceutical industries. Although the cost of certification was not considered as a barrier for the implementation of ISO 14001, the majority of the pharmaceutical industries are neither interested nor willing to adopt the Standard if they are not exposed to any regulatory pressure or external demand. They are more concerned with quality and safety issues with the most adopted international standard among the industries being the ISO 9001 quality management system. This study highlights the aspect that financial barriers are not always the hurdles for implementing environmental management strategies in developing countries and underscores the need for regulatory frameworks and enforcement.